The similar rates of occurrence of consonants across the world's languages: A quantitative analysis of phonetically transcribed word lists. (September 2018) - Everett, Caleb
Abstract: Via an analysis of nearly 7000 phonetically transcribed word lists representing every major linguistic family, this study examines the frequency with which languages use particular consonants. The results suggest that there is an underlying global similarity in the frequency of occurrence of these consonants. Some consonants are uncommon across the word lists, and do not occur frequently even in those languages in which they are used. In contrast, a few other consonants represent a large portion of sounds in the word lists, across regions and linguistic families. The analysis quantifies the pervasiveness of such sounds that are known to be, impressionistically, common in speech. A new method captures the overall similarity of consonants' rates of occurrence across languages and families. This method offers one means of evaluating the extent to which individual languages or families deviate from, or adhere to, the typical patterns of consonant usage. It is suggested that the crosslinguistic similarity of consonant usage, in terms of rates of occurrence in word lists, likely owes itself to previously documented factors like the relative ease of articulation of some sounds. This new evidence suggests that the role of ease of articulation in shaping speech may be more influential than generally assumed, though other explanatory factors are also likely at work and these patterns require further exploration with more robust intralinguistic phonetic corpora. Highlights: Languages are surprisngly similar in terms of how often they use many consonants. This paper offers a novel method of evaluating the overall similarity of consonants' rates of occurrence across languages. Ease of articulation- contributes to the inordinate frequency of some consonants.